Role of microglia autophagy and mitophagy in age-related neurodegenerative diseases - Lin, Mingkai; Yu, Hongwen; Xie, Qiuyan; Xu, Zhiyun; Shang, Pei (Frontiers in Aging Neuroscience, 2023)
Microglia, characterized by responding to damage, regulating the secretion of soluble inflammatory mediators, and engulfing specific segments in the central nervous system (CNS), are functioned as key immune cells in the CNS. Emerging evidence suggests that microglia coordinate the inflammatory responses in CNS system and play a pivotal role in the pathogenesis of age-related neurodegenerative diseases (NDDs). Remarkably, microglia autophagy involves the regulation of subcellular substances, which include the degradation of misfolded proteins and other harmful constituents produced by neurons. Therefore, microglia contributes to neuronal homeostasis maintenance and inhibition of neuroinflammation. In this review, we aimed at highlighting the pivotal role of microglia autophagy in the pathogenesis of age-related NDDs. Based on the mechanistic process and the co-interaction between microglia autophagy and different kinds of NDDs, we focused on potential therapeutic agents and approaches that can treat or attenuate the onset and progression of these diseases through modulating microglia autophagy, including promising nanomedicines. Our review provides a valuable reference for subsequent studies. We agree that the treatment of NDDs through modulation of microglia autophagy is a prospective measure. The exploration of microglia autophagy and the development of nanomedicines greatly enhance our understanding of NDDs.